The Influence of Salary and Job Satisfaction on Employee Performance in Customer-Oriented Business Environments - Ratnawita, Ratnawita; Fariz, Luthfi Ahmad; Edward, Yusuf Ronny; Rosita, Rosita; Putra, Ali Syah (Celebes Scholar pg, 2025)
The study looks at the link between salary, job satisfaction and employee performance in an SME in Demak Regency, Indonesia. Employing quantitative methods and multiple linear regression, information was collected using a census approach on 100 workers from CV Soerasi Mandiri. Results support that employee performance is strongly influenced by both their salary and job satisfaction. Salary motivates people from the outside by making them feel the job is fair and inspiring them to try harder, yet job satisfaction helps people work harder, feel happier and value their organization. Because the adjusted R² value is 0.779, these two variables, together, explain much of the differences in performance. These results underscore the practical importance of compensation and workplace satisfaction in sustaining individual productivity, especially in business environments that rely on high employee responsiveness, brand representation, and service quality. The study offers actionable insights for human resource management practices in dynamic sectors, including those increasingly shaped by digital interaction and consumer-facing roles.